Artificial Intelligence for 6G - Kim, Haesik; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook introduces Artificial Intelligence (AI) techniques for wireless communications and networks, helping readers to find solutions for communications and network problems using AI. Artificial Intelligence for 6G introduces, in a step-by-step manner, AI techniques such as: unsupervised learning; supervised learning; reinforcement learning; and deep learning. It explains how these techniques can be used for wireless communications and network systems, particularly in designing and optimizing 6G networks. This book is at the forefront of 6G research, and will be of interest internationally, to graduate students, academics, engineers, and developers who are focused on future development of network systems and mobile communications. .
Part I: Artificial Intelligence Techniques -- Chapter 1. Historical Sketch of Artificial Intelligence -- Chapter 2. Unsupervised Learning -- Chapter 3. Supervised Learning -- Chapter 4. Gradient Descent -- Chapter 5. Reinforcement Learning -- Chapter 6. Deep Learning -- Part II: Artificial Intelligence Enabled Techniques for 6G -- Chapter 7. Artificial Intelligence and 6G -- Chapter 8. AI for Big Data -- Chapter 9. AI Enabled Wireless Communications -- Chapter 10. AI Enabled Networks -- Chapter 11. AI Empowered Mobile Applications.
Keywords: Wireless communication systems; Mobile communication systems; Artificial intelligence; Cooperating objects (Computer systems).; Mathematical optimization; Wireless and Mobile Communication; Artificial Intelligence; Cyber-Physical Systems; Optimization; Machine learning; Wireless communication systems -- Data processing